Role of Long Non-coding RNAs on Bladder Cancer - Li, Hui-Jin; Gong, Xue; Li, Zheng-Kun; Qin, Wei; He, Chun-Xia; Xing, Lu; Zhou, Xin; Zhao, Dong; Cao, Hui-Ling (Frontiers in Cell and Developmental Biology, 2021)
The early diagnosis for bladder cancer (BC), the most common malignant tumours in the urinary system, is essential to improve the prognosis and overall survival of patients. However, there are few biomarkers with high sensitivity and high specificity for BC diagnosis. Multiple long noncoding RNAs (lncRNAs) are abnormally expressed in BC, and play an important role in the tumorigenesis of BC. Herein, this review summarized the expression, function, and related genes or signaling pathways of lncRNAs, and the clinical significance of lncRNAs in the diagnosis and molecular mechanism of BC. There are more than one hundred lncRNAs abnormally expressed in BC, which are involved in regulating proliferation, cell cycle, apoptosis, migration, invasion, metabolism and drug resistance of BC. Meanwhile, the abnormal expression of forty-five lncRNAs is closely related to multiple clinical parameters of BC, including tumour size, metastasis, invasion, tumour lymph node metastasis stage, diagnosis and prognosis of BC. Additionally, the molecular mechanisms of lncRNAs in BC, including lncRNAs interacting with DNA, RNA and protein, was explored. This review would provide novel strategies and biomarkers for the diagnosis and treatment of BC base on lncRNAs.